2009
DOI: 10.1007/s10071-009-0249-5
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkeys (Macaca mulatta) adaptively monitor uncertainty while multi-tasking

Abstract: As researchers explore animals’ capacity for metacognition and uncertainty monitoring, some paradigms allow the criticism that animal participants—who are always extensively trained in one stimulus domain within which they learn to avoid difficult trials—use task-specific strategies to avoid aversive stimuli instead of responding to a generalized state of uncertainty like that humans might use. We addressed this criticism with an uncertainty-monitoring task environment in which four different task domains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 35 publications
0
58
1
1
Order By: Relevance
“…Yet again, humans ( Figure 2A) and monkeys ( Figure 2B) displayed an increase in the use of the UR corresponding with a decrease in use of the categorization responses for the most difficult trials. Other experiments explored metacognition in rhesus monkeys and showed that the use of the UR or other metacognitive responses transfers across a variety of different tasks (Basile, Schroeder, Brown, Templer, & Hampton, 2015;Brown, Templer, & Hampton, 2017;Kornell, Son, & Terrace, 2007;Smith, Redford, Beran, & Washburn, 2010;Templer & Hampton, 2012) and that monkeys will continue using the UR when feedback is delayed (Smith, Beran, Redford, & Washburn, 2006), minimizing the likelihood that task-specific environmental cues are responsible for the use of the UR. Figure 1. A.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
“…Yet again, humans ( Figure 2A) and monkeys ( Figure 2B) displayed an increase in the use of the UR corresponding with a decrease in use of the categorization responses for the most difficult trials. Other experiments explored metacognition in rhesus monkeys and showed that the use of the UR or other metacognitive responses transfers across a variety of different tasks (Basile, Schroeder, Brown, Templer, & Hampton, 2015;Brown, Templer, & Hampton, 2017;Kornell, Son, & Terrace, 2007;Smith, Redford, Beran, & Washburn, 2010;Templer & Hampton, 2012) and that monkeys will continue using the UR when feedback is delayed (Smith, Beran, Redford, & Washburn, 2006), minimizing the likelihood that task-specific environmental cues are responsible for the use of the UR. Figure 1. A.…”
Section: Successes In Animal Metacognition Tests -Primarily Primatesmentioning
confidence: 99%
“…For example, researchers [35] asked macaques to monitor uncertainty while multi-tasking. Four different difficult discriminations were randomly intermixed trial by trial.…”
Section: Testing Low-level Interpretations Of Animal Metacognitionmentioning
confidence: 99%
“…To address this concern, researchers removed the reward contingency for that response [19,22,35]. In one case [22], macaques judged whether arrays were less or more numerous than a session-specific numerosity.…”
Section: Testing Low-level Interpretations Of Animal Metacognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a number of comparative psychologists have claimed to find evidence of metacognitive abilities in primates who seem to lack equivalent mindreading abilities [15][16][17][18][19][20][21][22][23]. They suggest that the evolution of these first-person monitoring-and-control abilities would have provided the foundation for the later evolution of third-person mindreading [24].…”
Section: Introductionmentioning
confidence: 99%